2021
DOI: 10.1021/acsami.0c22387
|View full text |Cite
|
Sign up to set email alerts
|

Building Tailored Interfaces through Covalent Coupling Reactions at Layers Grafted from Aryldiazonium Salts

Abstract: Aryldiazonium ions are widely used reagents for surface modification. Attractive aspects of their use include wide substrate compatibility (ranging from plastics to carbons to metals and metal oxides), formation of stable covalent bonding to the substrate, simplicity of modification methods that are compatible with organic and aqueous solvents, and the commercial availability of many aniline precursors with a straightforward conversion to the active reagent. Importantly, the strong bonding of the modifying lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 210 publications
1
25
0
Order By: Relevance
“…SLG/SiO 2 represents the most commonly used type of surface-supported graphene and is mass-produced. Diazonium chemistry was used for the covalent modification of SLG/SiO 2 as it remains one of the most efficient and versatile strategies for attaching organic functional groups to the basal plane of carbon surfaces , including graphene Figure shows a schematic of the overall procedure used for the multicomponent covalent patterning together with the molecular structures of the diazonium salts.…”
Section: Resultsmentioning
confidence: 99%
“…SLG/SiO 2 represents the most commonly used type of surface-supported graphene and is mass-produced. Diazonium chemistry was used for the covalent modification of SLG/SiO 2 as it remains one of the most efficient and versatile strategies for attaching organic functional groups to the basal plane of carbon surfaces , including graphene Figure shows a schematic of the overall procedure used for the multicomponent covalent patterning together with the molecular structures of the diazonium salts.…”
Section: Resultsmentioning
confidence: 99%
“…Ethynyl groups offer good possibilities for post-functionalization via alkyne Click chemistry. [11,32,33] The layered surface could be customized in terms of pore size and polarity to further improve SEI formation and lithium-ion (de)intercalation and help to reduce irreversible capacity loss.…”
Section: Chemelectrochemmentioning
confidence: 99%
“…The grafting of aryl diazonium salts (ADS) to a variety of surfaces, including carbon‐based materials has been extensively studied [6–12] . Leroux and Hapiot [13] reported that the grafting density of electrografted ethynyl diazonium salts on glassy carbon can be tuned by varying the size of the protecting group.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary surface modifiers have transformed grafting research methodologies from academic interest to industrial and medicinal applications. [1][2][3][4][5][6][7][8][9][10] Jean Pinson and co-workers were the first to report the mechanism of a reductive strategy and the strong binding of aryl groups on glassy carbon electrodes. 4 Surface modification by organic functional groups, which formed covalent bonds with the surface established the use of aryldiazonium salts as coupling agents and surface modifiers in materials science research.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of materials have been subjected to diazonium modifications, and data from research laboratories around the world have been compiled in review papers and book chapters. 1,9,10 The focus of this feature article is on the conceptual development of diazonium salts as surface modifiers for gold nanoparticles and flat surfaces, and their applications in forensics, nanomedicine engineering, sensors, energy, and catalysis. We discuss the efficient use of aryldiazonium salts for the generation of aryl-capped gold nanoparticles and flat gold surfaces.…”
Section: Introductionmentioning
confidence: 99%